Application of Smart Aquaponics Technology for Sustainable Household-Scale Food Production in Urban Jakarta - Prastika Suwandi Tjeng; Rashid Rahman; Rina Nopianti; Ravi Dara (Yayasan Adra Karima Hubbi, 2025)
Background. Rapid urbanization in Jakarta has intensified challenges related to food security, limited land availability, and environmental degradation, prompting the need for sustainable household-scale food production systems. This study explores the application of smart aquaponics technology as an integrated model combining aquaculture and hydroponics for efficient food production within urban households. Purpose. The research aims to assess the technological feasibility, productivity outcomes, and environmental benefits of smart aquaponics as a sustainable alternative to conventional urban farming methods. Method. A mixed-method design was employed, incorporating experimental trials, sensor-based monitoring, and household surveys conducted between January and August 2024 across five Jakarta districts.. Results. Results indicate that smart aquaponics systems increased vegetable yield by 38% and reduced water consumption by 42% compared to traditional hydroponic setups. The integration of IoT sensors enabled automated nutrient control, improving fish growth rates and system stability. Respondents reported enhanced household food self-sufficiency and reduced monthly food expenditure. Conclusion. The study concludes that smart aquaponics offers a scalable and environmentally friendly solution for urban food resilience, aligning with Indonesia’s Sustainable Development Goals on food security and environmental sustainability.